A homozygous loss-of-function mutation in inositol monophosphatase 1 (IMPA1) causes severe intellectual disability - Figueiredo, T; Melo, U S; Pessoa, A L S; Nobrega, P R; Kitajima, J P; Rusch, H; Vaz, F; Lucato, L T; Zatz, M; Kok, F; Santos, S (Molecular psychiatry, 2016)
The genetic basis of intellectual disability (ID) is extremely heterogeneous and relatively little is known about the role of autosomal recessive traits. In a field study performed in a highly inbred area of Northeastern Brazil, we identified and investigated a large consanguineous family with nine adult members affected by severe ID associated with disruptive behavior. The Genome-Wide Human SNP Array 6.0 microarray was used to determine regions of homozygosity by descent from three affected and one normal family member. Whole-exome sequencing (WES) was performed in one affected patient using the Nextera Rapid-Capture Exome kit and Illumina HiSeq2500 system to identify the causative mutation. Potentially deleterious variants detected in regions of homozygosity by descent and not present in either 59 723 unrelated individuals from the Exome Aggregation Consortium (Browser) or 1484 Brazilians were subject to further scrutiny and segregation analysis by Sanger sequencing. Homozygosity-by-descent analysis disclosed a 20.7-Mb candidate region at 8q12.3-q21.2 (lod score: 3.11). WES identified a homozygous deleterious variant in inositol monophosphatase 1 ( IMPA1 ) (NM_005536), consisting of a 5-bp duplication (c.489_493dupGGGCT; chr8: 82,583,247; GRCh37/hg19) leading to a frameshift and a premature stop codon (p.Ser165Trpfs*10) that cosegregated with the disease in 26 genotyped family members. The IMPA1 gene product is responsible for the final step of biotransformation of inositol triphosphate and diacylglycerol, two second messengers. Despite its many physiological functions, no clinical phenotype has been assigned to this gene dysfunction to date. Additionally, IMPA1 is the main target of lithium, a drug that is at the forefront of treatment for bipolar disorder.